Classification, preference and perception of Chinese and Spanish university students’ subject lines - Rodríguez Velasco, David (Círculo de Lingüística Aplicada a la Comunicación, 2025)
The subject line is a textual category that maintains a close relationship with the body of the message and combined with other data in the header, such as the date and the name of the sender, allows the content of the message to be summarized objectively. Subject lines have been largely studied in relation to its content, length and impact on the recipient, however, the results are mixed. The present work aims to analyse the preference of use, the function and the effect that the subject line has in the computermediated communication (CMC) in an academic context. To analyse and classify the uses and preferences of the subject lines, 262 emails sent by Spanish (n = 38) and Chinese (n = 224) university students to a member of the faculty were studied and contrasted with the perception of a group of teachers (n = 14) in relation to its suitability and relevance to the context. Results show a tendency towards its omission in both groups. When used, both Spanish and Chinese students preferred to make references to the content of the message. The analyses of teachers’ perception showed the need to instruct university students in the correct writing of emails.